Creativity and Dissidence in Jordanian Women’s Literature - Amin, Omnia (Respectus Philologicus, 2015)
Contemporary Jordanian women writers have transported the act of writing into an act of dissidence to reflect their own perspectives and priorities shaped by a distinctive cultural and aesthetic formation. Writers like Huzama Habayeb, Afaf Batayneh, and Leila Elatrash speak with assertive voices about the confinement and even the abuse of Arab women. Their works reveal an unequivocal sense of pride in overthrowing all confinements, while at the same time condemning and combating the abusive excesses of patriarchy when it appropriates and exploits religious and cultural traditions to preserve its own material hegemony. Their discourse strives, with varying degrees of militancy, for an agenda that is quite dissident and threatening to the fabric of the traditional religious and social Arab norms. Some look at the West for a substitute model of their freedom of expression, while others seek an answer within the framework of Arabic culture. Their writing represents not only a fascinating phenomenon of articulating feelings and perspectives of their own by adopting a dissident stance in their use of language and narrative, but also a promise to extend and expand their scope of focus to an apparent militant and confrontational response to the discourse produced by male-made theocracies.